Has the UK living kidney donor population changed over time? A cross-sectional descriptive analysis of the UK living donor registry between 2006 and 2017. Issue 6 (15th June 2020) - Bailey, Phillippa K; Wong, Katie; Robb, Matthew; Burnapp, Lisa; Rogers, Alistair; Courtney, Aisling; Wroe, Caroline
Abstract : Background: A living-donor kidney transplant is the best treatment for most people with kidney failure. Population cohort studies have shown that lifetime living kidney donor risk is modified by sex, age, ethnicity, body mass index (BMI), comorbidity and relationship to the recipient. Objectives: We investigated whether the UK population of living kidney donors has changed over time, investigating changes in donor demographics. Design: We undertook a cross-sectional analysis of the UK living kidney donor registry between January 2006 to December 2017. Data were available on living donor sex, age, ethnicity, BMI, hypertension and relationship to recipient. Setting: UK living donor registry. Participants: 11 651 consecutive living kidney donors from January 2006 to December 2017. Outcome measures: Living kidney donor demographic characteristics (sex, age, ethnicity, BMI and relationship to the transplant recipient) were compared across years of donation activity. Donor characteristics were also compared across different ethnic groups. Results: Over the study period, the mean age of donors increased (from 45.8 to 48.7 years, p<0.001), but this change appears to have been limited to the White population of donors. Black donors were younger than White donors, and a greater proportion were siblings of their intended recipient and male. The proportion of non-genetically related non-partner donations increased over the 12-year period of analysis (p value for linear trend=0.002). Conclusions: The increasing age of white living kidney donors in the UK has implications for recipient and donor outcomes. Despite an increase in the number of black, Asian and minority ethnic individuals waitlisted for a kidney transplant, there has been no increase in the ethnic diversity of UK living kidney donors. Black donors in the UK may be at a much greater risk of developing kidney failure due to accumulated risks: whether these risks are being communicated needs to be investigated.